On the sound absorption performance of a felt sound absorber. (15th December 2016) - Meriç, Cem; Erol, Haluk; Özkan, Aytekin
Abstract: In this work, we have developed an analytical model of a multilayer porous material based on the transfer matrix method to predict the absorption behavior at plane wave incidence. The aim of this study is to modify/tune the sound absorption coefficient of a felt to obtain an improved absorbing performance in the mid frequency range without increasing its weight. To achieve this target, the developed model has been used to find the best combination of each layer type and thickness. The analytical results were validated by test results.